Sustainability as an Input for the Design of Olympic Villages - Doralp, Banu; Barkul, Omur (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
Since the 1960s, hosting the Olympic Games has been seen as an opportunity to create urban development. The post-Games use of sport venues, the fulfillment of a city's housing needs by using Olympic Village buildings and the renewal of transport and other infrastructure that accompanies hosting of the Games may be considered indicators for the success of the International Olympic Games. But the city and its citizen do not benefit from these investments in the design of new structures if that design is not carried out in the light of well-planned urban development projecting. Local and international studies on sustainability, particularly since the 1980s, have shown that sustainable urbanization is only achievable with sustainable development planning. Therefore economic, social and environmental development needs to be provided. If the last Olympic cities are examined in relation to this aspect, it will be seen that an understanding of such factors is reflected in their development. Throughout the history of the modern Games host cities have considered them as an opportunity for development, but cities are now heading towards the implementation of more sensitive actions for the future generation, social and environmental values with the improvement in the approach of sustainable development.
Keywords: Olympic games; olympic villages; sustainability; sustainable olympic games; sustainable urbanization; Architecture